Enzyme-triggered size shrink and laser-enhanced NO release nanoparticles for deep tumor penetration and combination therapy. (June 2018) - Hu, Chuan; Cun, Xingli; Ruan, Shaobo; Liu, Rui; Xiao, Wei; Yang, Xiaotong; Yang, Yuanyuan; Yang, Chuanyao; Gao, Huile
Abstract: Chemotherapy remains restricted by poor drug delivery efficacy due to the heterogenous nature of tumor. Herein, we presented a novel nanoparticle that could not only response to the tumor microenvironment but also modulate it for deep tumor penetration and combination therapy. The intelligent nanoparticle (IDDHN) was engineered by hyaluronidase (HAase)-triggered size shrinkable hyaluronic acid shells, which were modified with NIR laser sensitive nitric oxide donor (HN), small-sized dendrimeric prodrug (IDD) of doxorubicin (DOX) as chemotherapy agent and indocyanine green (ICG) as photothermal agent into a single nanoparticle. IDDHN displayed synergistic deep penetration both in vitro and in vivo, owing to the enzymatically degradable HN shell mediated by HAase and laser-enhanced NO release triggered deep penetration upon strong hyperthermia effect of ICG under the NIR laser irradiation. The therapeutic effect of IDDHN was verified in 4T1 xenograft tumor model, and IDDHN showed a much better antitumor efficiency with few side effects upon NIR laser irradiation. Therefore, the valid of this study might provide a novel tactic for engineering nanoparticles both response to and modulate the tumor microenvironment for improving penetration and heterogeneity distribution of therapeutic agents in tumor. Graphical abstract: